The effects of marketing mix strategies on car buyers' satisfaction (a case of Pantai Bharu Holdings Sdn. Bhd.) / Mohd Nahar Faiz Mohd Nasir - Mohd Nasir, Mohd Nahar Faiz (Faculty of Business and Management, 2007)
The Malaysian Automotive Association (MAA) has forecast car sales to rise slightly this year to 500,000 units from the 490,768 units sold in 2006. Optimism aside, it has to be noted that the vehicle market in Malaysia is at its saturation point, with vehicle ownership penetration rate among the highest in the world. An analyst with a local stock broking firm mentioned that only a few cars can the market absorbs, especially after record car sales in 2004 and 2005. Such momentum is not sustainable, so it was no surprise that sales fell. Moreover, it is still too early for the replacement cycle to take place for those who bought cars in 2004 and 2005, as the normal replacement cycle is four or five years. Pantai Bharu Holdings Sdn. Bhd. intends to increase the sales volume of the reconditioned car and thus the company has to restrategize the marketing mix program in order to attract more potential buyer to come and buy their product. The primary objective for the research on Pantai Bharu Holdings Sdn. Bhd. is to identify the level of customer satisfaction, to determine the most appropriate marketing mix which will be competitive edge over car industry rivals and to consult Pantai Bharu Holdings Sdn Bhd management recommendations to group marketing mix. In the research methodology, this research used a descriptive method whereby it describes the characteristics of relevant group such as customers of Pantai Bharu Holdings Sdn. Bhd. The goal of descriptive study, hence, is to offer the researcher, a profile or to describe relevant aspects of the phenomena of interest from an individual, organizational, industry-oriented, or other perspective. For the sampling technique, it applied the systematic random sampling, taken at K interval =20 and thus, the total respondent is 50 from 250 buyers during 2006. The overall findings of mean value from 50 respondents shows that most valuable aspect in the marketing mix program of Pantai Bharu Holdings is Place where it consists the highest total average of the mean value among others (3.99). Next, Price and Product consists the same value (3.86) but when they are compare with the total average of the standard deviation , Price is considered as the second place because the lower standard deviation (0.93) while Product is (0.95). Lastly, the lowest total average of mean value is Promotion (3.79). When the research proceeds to the hypothesis testing, Place again in the first place with the P value is 0.710 consistent with the highest mean value before. Here, the research concludes that Place - one of the marketing mix strategies in Pantai Bharu Holdings Sdn. Bhd was the most important factor in customer satisfaction at the company. Recommendations and suggestion on how to increase the sales volume and perceived satisfaction towards customers of Pantai Bharu Holdings Sdn. Bhd. Have been identified and stated at the end of the research. Furthermore, implications for future research is also being discussed for achieving further involvement in fields of ¬benefits and perceived satisfaction of Pantai Bharu Holdings Sdn. Bhd.